Differential lateralization of hippocampal connectivity reflects features of recent context and ongoing demands: An examination of immediate post‐task activity. Issue 2 (8th October 2014) - Hartzell, James F.; Tobia, Michael J.; Davis, Ben; Cashdollar, Nathan M.; Hasson, Uri
Abstract Neuroimaging studies have shown that task demands affect connectivity patterns in the human brain not only during task performance but also during subsequent rest periods. Our goal was to determine whether ongoing connectivity patterns during rest contain information about both the current rest state, as well as the recently terminated task. Our experimental design consisted of two types of active tasks that were followed by two types of low‐demand rest states. Using this design, we examined whether hippocampal functional connectivity during wakeful rest reflects both features of a recently terminated task and those of the current resting‐state condition. We identified four types of networks: (i) one whose connectivity with the hippocampus was determined only by features of a recently terminated task, (ii) one whose connectivity was determined only by features of the current resting‐state, (iii) one whose connectivity reflected aspects of both the recently terminated task and ongoing resting‐state features, and (iv) one whose connectivity with the hippocampus was strong, but not affected by any external factor. The left and right hippocampi played distinct roles in these networks. These findings suggest that ongoing hippocampal connectivity networks mediate information integration across multiple temporal scales, with hippocampal laterality moderating these connectivity patterns. Hum Brain Mapp 36:519–537, 2015. © 2014 Wiley Periodicals, Inc.